Implementasi Tontonan Video Edukasi Ilmu Pengetahuan Sosial Sebagai Media Pembelajaran Siswa di MIN 7 Kota Medan - Syarifah Syarifah; Eka Yusnaldi (LP. Ma'arif Janggan Magetan, 2023)
Technological advances have had a major influence on the development of learning, one of which is by providing educational videos which are carried out at MIN 7 Medan City. The purpose of this article is to reveal how to implement educational videos in social studies learning with the following focus. First, how to plan educational video media in social studies learning at MIN 7 Medan City. Second, make the implementation and student learning outcomes of the use of educational videos. Third, what are the obstacles in implementing educational videos in social studies learning and the solutions to these obstacles. This study uses a qualitative descriptive approach, with the method of collecting data through interviews, observation, and documentation. Then, to ensure the validity of the data is used through triangulation. The research results obtained as follows. First, in planning lessons using educational video media, it is the duty of the principal and teacher to plan learning in class according to the RPP and develop it. Second, in the implementation of the lesson, it has displayed videos obtained from Youtube in the form of videos of short duration ± 10 minutes when learning is in progress. Third, there are still obstacles felt by teachers and students related to learning such as managing time and teacher skills in designing videos. However, solutions are carried out by teachers such as intense discussions between teachers and students, sharing video selection, and learning innovations. So it can be concluded that the implementation of learning using educational videos is very helpful for teachers and students as a learning support tool in the ongoing learning process.